Presence of Pain Shows Greater Effect than Tendon Structural Alignment During Landing Dynamics - Silvia Ortega-Cebrián; Diogo C. F. Silva; Daniela F. Carneiro; Victor Zárate; Leonel A. T. Alves; Diana C. Guedes; Carlos A. Zárate-Tejero; Aïda Cadellans-Arróniz; António Mesquita Montes (Journal of Functional Morphology and Kinesiology)
Background/Objectives: Eccentric loading during landing is considered a key factor in the development of patellar tendinopathy and is associated with stiff landings and patellar tendinopathy. This study aims to investigate the relationship between tendon structure, presence of pain, and sex differences in landing kinematics and kinetics during countermovement jumps (CMJ) and tuck jump tests (TJT) in professional volleyball players. Methods: Professional volleyball players aged 18 to 30 years old (14 females and 25 males) participated in a cross-sectional study. Data included the Victorian Institute of Sport Assessment Patellar Tendon (VISA-P) questionnaire; patellar tendon ultrasound characterization tissue (UTC) scans, in order to identify groups with misaligned tendon fibers (MTF) or aligned tendon fibers (ATF); and biomechanical assessments for CMJ and TJT. The joint angle (JA) at the lower limb was measured at peak ground reaction force (peak_vGRF) and maximal knee flexion (max_KF). A general linear model was used to evaluate joint JA differences between tendon alignment, pain, and sex variables. Sample t-tests compared peak_vGRF, load time, load rate, and area based on tendon alignment, pain presence, sex, and jump. The statistical significance of p-value is >0.05, and the effect size (ES) was also calculated. Results: The MTF group revealed decreased knee JA during TJT at peak_vGRF (p = 0.01; ES = −0.66) and max_KF (p = 0.02; ES = −0.23). The presence of pain was associated with increased JA during the CMJ, particularly at peak_vGRF and max_KF for trunk, hip, and ankle joints. Females showed decreased peak_vGRF than males. Landing with misaligned tendon fibers showed longer load times compared to aligned tendon fibers (p = 0.021; ES = −0.80). The TJT exhibited a greater load rate than the CMJ (p = 0.00; ES = −0.62). Conclusions: Pain is a critical factor influencing greater JA during landing, particularly at the trunk, hip, and ankle joints in CMJ. Misaligned tendon fibers compromise landing dynamics by increasing trunk JA during TJT. Kinetics varied significantly by sex and jump type, while pain and tendon structure revealed limited differences.